Kesehatan Mental dalam Pendidikan Islam : Studi Hadis Tematik Tentang Ketenangan Jiwa dan Relevansinya Dalam Psikologi Positif - Ernisah; Muhammad Alif; Refa Hudan Lisalam (STAI Nurul Qadim, 2025)
Mental health is a fundamental aspect in the educational process, especially in forming students who are emotionally and spiritually resilient. This article aims to examine the hadiths of the Prophet Muhammad SAW related to peace of mind (sakīnah, ṭuma'nīnah, ṣabr, tawakkal, and ridha) through a thematic study approach (maudu'i), and to analyze their relevance within the framework of contemporary positive psychology. This study is qualitative with a library method, where primary data in the form of authentic hadiths are collected, classified thematically, and analyzed for their meaning in the context of mental health. The results of the study indicate that the values contained in the hadiths have a high degree of conformity with concepts in positive psychology such as resilience, gratitude, mindfulness, and inner peace. These findings provide a foundation for the integration of Islamic values in mental health-based education, especially in the development of Islamic guidance and counseling programs in schools. Thus, this study confirms that the Prophet's hadiths not only have spiritual-theological value, but also contribute applicatively to strengthening students' mental health.